Assessment of Trichogramma species (Hymenoptera: Trichogrammatidae) for biological control in cassava (Manihot esculenta Crantz) - Soares, Marcus Alvarenga; Leite, Germano Leão Demolin; Zanuncio, José Cola; Ferreira, Cleidson Soares; Rocha, Silma Leite; Sá, Veríssimo Gibran Mendes de (Acta Scientiarum. Agronomy, 2014)
Cassava is the sixth most important crop in the world, and it is attacked by many pests, such as Erinnyis ello (L.) (Lepidoptera: Sphingidae). This lepidopteran pest has natural enemies that can efficiently control its population, such as Trichogramma spp. (Hymenoptera: Trichogrammatidae). The objective of this research was to assess the flight capacity, parasitism and emergence of Trichogramma pretiosum, T. marandobai and T. demoraesi and to select the most efficient species among them for biological control programs. The flight capacity of these species was assessed in test units consisting of a plastic PVC cylinder with a rigid, transparent plastic circle on the upper portion of the cylinder and an extruded polystyrene disk to close the bottom of the cylinder. A tube was placed in each test unit containing a card with 300 Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) eggs that had been parasitised by Trichogramma. These cards were later assessed to determine the parasitism rate and adult emergence of these natural enemies. Trichogramma pretiosum presented the highest flight capacity (68 ± 5%), parasitism (74 ± 2%) and percentage of adults emerged (91 ± 3%) in the laboratory, making this species suitable for mass rearing and release in biological control programs.